1996
DOI: 10.1093/intimm/8.11.1643
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an active soluble form of human CD38 in normal and pathological fluids

Abstract: Human CD38 is a transmembrane glycoprotein involved in lymphocyte activation and adhesion to endothelium. The ectocellular domain of the molecule possesses properties of a bifunctional enzyme catalyzing both the synthesis from NAD+ and the hydrolysis of the calcium-releasing metabolite cyclic ADP-ribose (cADPR). Surface expression of CD38 (mCD38) is rapidly and almost completely down-modulated upon ligation by specific mAb in cells from different lineages. The data presented here also show that, in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 0 publications
6
57
0
1
Order By: Relevance
“…Once there, CD38 can undergo shedding and internalization. A soluble form of human CD38 with a M r ϭ 39,000 was identified in the culture supernatants of mixed lymphocyte cultures and CD38 ϩ leukemic cell lines such as Raji (a Burkitt lymphoma) and Supt-1 (a T-acute lymphoblastic leukemia) [19] (Fig. 1).…”
Section: Dynamics Of Surface Cd38mentioning
confidence: 99%
See 3 more Smart Citations
“…Once there, CD38 can undergo shedding and internalization. A soluble form of human CD38 with a M r ϭ 39,000 was identified in the culture supernatants of mixed lymphocyte cultures and CD38 ϩ leukemic cell lines such as Raji (a Burkitt lymphoma) and Supt-1 (a T-acute lymphoblastic leukemia) [19] (Fig. 1).…”
Section: Dynamics Of Surface Cd38mentioning
confidence: 99%
“…For example, in 1998 it was reported that anti-CD38 mAb-reactive proteins in human serum are more abundant in cancer patients than in healthy controls [21]. Individuals with multiple myeloma can also have large amounts of soluble CD38 in their serum, ascites, and urine [19]. Amniotic fluid is also rich in soluble CD38 [19].…”
Section: Dynamics Of Surface Cd38mentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, mature virgin and memory B lymphocytes express low levels of the molecule. CD38 also is found in soluble form in normal and pathological fluids (15) and in exosomes, which are membrane vesicles secreted by B cells and likely a component of an intercellular communication network (16). Clinical routine confirms that the cells of the myeloma clone do express CD38 in the overwhelming majority of patients, although at varying surface densities.…”
Section: Cd38 In Myelomamentioning
confidence: 95%